Prevalence of falls among older people attending a primary care clinic in Kuala Lumpur, Malaysia. - Shariff Ghazali, Sazlina; R., Krishnan; Azhar Shah, Shamsul; Ahmad, Zaiton; R., Visvanathan (Universiti Kebangsaan Malaysia, 2008)
Introduction : The aim of this study was to determine the prevalence and the pattern of falls in community dwelling older people attending a primary care clinic in Kuala Lumpur, Malaysia.